Why should a Business English Teacher be a Constructivist Teacher? - Lempart, Joanna (Glottodidactica, 2008)
The article provides some considerations related to the issue of learning and teaching Business English in Poland. It explains the difference between Business English, General English and English for Specific Purposes. The main aim of it is to present the characteristics of the Constructivist Business English Teachers. In order to this the constructivist approach to second language learning and teaching is briefly presented and a few. valuable suggestions are provided on how to it can be employed in Business English teaching.